No Price Like Home: Global House Prices, 1870 – 2012 - Thomas Michael Steger; Katharina Knoll; Moritz Schularick (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
No Price Like Home: Global House Prices, 1870 – 2012
Keywords: Z00; Z10; Z11; 330